Effect of oxygen content of powder on microstructure and mechanical properties of hot isostatically pressed superalloy Inconel 718 - Rao G.A.; Srinivas M.; Sarma D.S. (My University, 2025)
Inert gas atomized (IGA) superalloy Inconel 718 powders with varied oxygen levels of 275, 180 and 140 ppm were consolidated by hot isostatic pressing (HIPing) at 1200 °C/120 MPa/3 h. The microstructural characterization of as-HIPed alloys has shown that the densification phenomenon of the powder does not depend on its oxygen content. However, the formation of deleterious phases such as prior particle boundaries (PPBs) occur more predominantly in the HIPed material produced from the powder with high oxygen content. It was also observed that the recrystallization and formation of annealing twins in the HIPed alloy are greatly influenced by the oxygen content. Transmission electron microscopy (TEM) studies have revealed that the precipitation of γ″, γ′ and δ phases does not depend on oxygen level of HIPed alloy during heat treatment as per AMS 5662J standard schedule but the MC carbides enriched with Nb and Ti precipitated preferentially at the PPBs for the alloy with high oxygen content of 275 ppm. In contrast, the carbides were found to be precipitated more uniformly in the matrix of the alloy with low oxygen content of 140 ppm. Tensile properties of the as-HIPed and HIP + heat treated alloys have shown that the yield strength (YS), ultimate tensile strength (UTS) do not get influenced by the oxygen content, but the ductility was found to be deteriorated drastically at elevated temperatures with increasing the oxygen content of the alloy. Stress rupture properties of the heat treated alloys at 650 °C under a stress level of 690 MPa have maintained a direct relation with the oxygen content, as the alloy with 275 ppm of oxygen content has shown inferior rupture life of 27 h with 2.1% ductility as compared to 84.5 h of life with 4.5% ductility and 116 h of life with 6% ductility offered by the alloys with 180 and 140 ppm of oxygen content, respectively. A better combination of mechanical properties achieved by use of prealloyed powder with low oxygen content makes it possible to explore the near net shape advantage of HIP technology to its maximum potential for alloy 718 components. © 2006 Elsevier B.V. All rights reserved.